2019
DOI: 10.1002/app.47679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platinum compounds/superfine aluminum hydroxide/ultrafine calcium carbonate on the flame retardation and smoke suppression of silicone foams

Abstract: Environmentally friendly, flame-retardant, and relatively low-density (0.25-0.31 g cm −3 ) silicone foams (SiFs) were successfully obtained through dehydrogenation at room temperature (RT = 25.0 C). Moreover, a flame-retardant system for SiFs was obtained through a synergistic combination of platinum (Pt) compounds, superfine aluminum hydroxide (ATH), and ultrafine calcium carbonate (CC). The smoke suppression, flame retardance, mechanical properties, and thermal stability of SiFs with Pt compounds, ATH, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The boiling point of the three additives (DMF at 193 • C, EHB at 297 • C, PHB at 133 • C) were lower than the 300 • C. As investigated before by TGA, the decomposition of the cellulose chains in the cotton samples mainly happened at temperature above 300 • C. It is deduced that the additives have already evaporated to flammable gas when the cotton is about to burn, making it burn more quickly and thoroughly thus reaching a higher pHRR. Different from the other three additives in this work, calcium sorbate is stable under temperature below 400 • C and one of its pyrolysis product-calcium carbonate can be used as a fire retardant filler [35,36]. The pHRR (88.5 kW/m 2 ) and THR (15.6 MJ/m 2 ) of cotton/CS were lower than that of pure cotton samples.…”
Section: Thermal Stability and Combustion Propertiesmentioning
confidence: 77%
“…The boiling point of the three additives (DMF at 193 • C, EHB at 297 • C, PHB at 133 • C) were lower than the 300 • C. As investigated before by TGA, the decomposition of the cellulose chains in the cotton samples mainly happened at temperature above 300 • C. It is deduced that the additives have already evaporated to flammable gas when the cotton is about to burn, making it burn more quickly and thoroughly thus reaching a higher pHRR. Different from the other three additives in this work, calcium sorbate is stable under temperature below 400 • C and one of its pyrolysis product-calcium carbonate can be used as a fire retardant filler [35,36]. The pHRR (88.5 kW/m 2 ) and THR (15.6 MJ/m 2 ) of cotton/CS were lower than that of pure cotton samples.…”
Section: Thermal Stability and Combustion Propertiesmentioning
confidence: 77%
“…On the contrary, after CPF‐6 was ignited, the flame propagation was very slow, and the foam remained intact after the test (see Figure 5c). This was mainly attributed to the good blocking effect of the mica/SGF‐armored skeleton in the foam framework and the pore wall, hindering the rapid propagation of the flame and exchange between the substance and the external environment 31–34 …”
Section: Resultsmentioning
confidence: 99%
“…This was mainly attributed to the good blocking effect of the mica/SGF-armored skeleton in the foam framework and the pore wall, hindering the rapid propagation of the flame and exchange between the substance and the external environment. [31][32][33][34] High temperature structural stability is also an important basis for evaluating the thermal protection performance of the PDMS composite foam. Figure 6 shows the microstructures of CPF-6 after the fire exposure at different temperatures (600-900 C) in the muffle furnace.…”
Section: Flame Retardant and Ceramifiable Propertiesmentioning
confidence: 99%
“…Mechanical properties are vital factors that affect the performance of SiFs . To investigate the effects of MAHP and zinc borate on the mechanical properties of the SiFs, the tensile strength and elongation at break of SiFs are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Verdejo et al synthesized flame‐retarded SiFs with carbon nanotubes, and the LOI increased as a function of carbon nanotube content, attaining the self‐extinguishing grade even at low mass fraction of the carbon nanotubes (0.5 wt%). Deng et al utilized platinum (Pt) compounds, superfine aluminum hydroxide (ATH), and ultrafine calcium carbonate (CC) as a flame‐retardant system for SiFs and deduced that the SiF with 0.6‐wt% Pt compounds, 15.0‐wt% ATH, and 15.0‐wt% CC exhibited the optimal comprehensive properties for smoke suppression, flame retardance, mechanical performance, and thermal stability. Kang et al found that with the same density, the LOI of SiFs could increase by 27.4% after adding 30‐wt% super fine talc powder and 1‐wt% hollow glass beads.…”
Section: Introductionmentioning
confidence: 99%